Vascular Adhesion Protein-1: A Cell Surface Amine Oxidase in Translation - Salmi Marko; Jalkanen Sirpa (MARY ANN LIEBERT, INC, 2022)
Significance: Vascular adhesion protein-1 (VAP-1) is an ectoenzyme that oxidates primary amines in a reaction producing also hydrogen peroxide. VAP-1 on the blood vessel endothelium regulates leukocyte extravasation from the blood into tissues under physiological and pathological conditions.
Recent Advances: Inhibition of VAP-1 by neutralizing antibodies and by several novel small-molecule enzyme inhibitors interferes with leukocyte trafficking and alleviates inflammation in many experimental models. Targeting of VAP-1 also shows beneficial effects in several other diseases, such as ischemia/reperfusion, fibrosis, and cancer. Moreover, soluble VAP-1 levels may serve as a new prognostic biomarker in selected diseases.
Critical Issues: Understanding the contribution of the enzyme activity-independent and enzyme activity-dependent functions, which often appear to be mediated by the hydrogen peroxide production, in the VAP-1 biology will be crucial. Similarly, there is a pressing need to understand which of the VAP-1 functions are regulated through the modulation of leukocyte trafficking, and what is the role of VAP-1 synthesized in adipose and smooth muscle cells.
Future Directions: The specificity and selectivity of new VAP-1 inhibitors, and their value in animal models under therapeutic settings need to be addressed. Results from several programs studying the therapeutic potential of VAP-1 inhibition, which now are in clinical trials, will reveal the relevance of this amine oxidase in humans.